2019
DOI: 10.1038/s41598-019-47815-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure functional insights into calcium binding during the activation of coagulation factor XIII A

Abstract: The dimeric FXIII-A 2 , a pro-transglutaminase is the catalytic part of the heterotetrameric coagulation FXIII-A 2 B 2 complex that upon activation by calcium binding/thrombin cleavage covalently cross-links preformed fibrin clots protecting them from premature fibrinolysis. Our study characterizes the recently disclosed three calcium binding sites of FXIII-A concerning evolution, mutual crosstalk, thermodynamic activation profile, substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 66 publications
1
47
0
1
Order By: Relevance
“…Ca 2+ is an important factor in coagulation function ( 17 ), and it was significantly decreased in patients with severe COVID-19 infection. Thus, we examined indicators related to coagulation function in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ is an important factor in coagulation function ( 17 ), and it was significantly decreased in patients with severe COVID-19 infection. Thus, we examined indicators related to coagulation function in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ plays an important role in maintaining heart function and coagulation function ( 17 , 40 , 41 ). When testing serum electrolytes, we found that the levels of Na + , K + , and Cl − were all normal in COVID-19 infected patients, although the level of Ca 2+ in patients with severe COVID-19 infection was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium concentration was another important variable impacting peptide incorporation, with increased calcium concentrations being associated with increased peptide incorporation. Calcium binding to sites on FXIII facilitate conformational changes that form substrate-binding pockets and ultimately expose the active site [ 48 ]. The reaction conditions that maximized peptide incorporation were subsequently used for the reactions that functionalized fibrin with the oligo tethers.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining aptamers show no direct specificity for fibrinogen and α2AP binding sites but as our functional data suggests, they might still maintain allosteric control over fibrinogen binding and subsequent cross-linking. These aptamers are observed to bind to counter-surfaces around regions which have been demonstrated to affect substrate binding for e.g., calcium binding sites ( Supplementary Materials, Figure S6 ) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%